Prototype Development of Research And Community Service Web Based Information System (SIM-PPM) of LPPM Unimed - Baharuddin Baharuddin; Hesti Fibriasari; Tansa Trisna Astono Putri (Sean Institute, 2020)
The development of SIMPPM is indispensable for the development of an information system for the Research and Community Service Institute. Information system development will be developed through the web. Currently, LPPM has made the system which will continue to be developed according to the needs and will be integrated with the system at the University. The research object is the LPPM Unimed information system. The research method used was ADDIE (Analysis, Design, Development, Implementation, and Evaluation), the first thing to do was to conduct a needs analysis about the research and service process that switched from manual to IT-based. After finding out what are the requirements for the process of proposal, assessment, monitoring and evaluation to the final report, a model is designed in the system to address the needs of the research and community service implementation process. Then the initial design, a storyboard is developed so that researchers, reviewers and admins can carry out all the processes in the SIMPPM page. The implementation of the system is conducted by researchers/lecturers, by conducting trials and making improvements to the results of the main trials to involve a wider audience. From the test results, the evaluation of user satisfaction is improving than the conventional way. The results of this study resulted a website in the form of SIMPPM which is intended for prospective researchers and civil servants, operators and reviewers who will carry out the process of receiving proposals, selection to reporting. This study provides an innovation in the LPPM information system. This study makes the development of an information system web based so that it can be used independently and anywhere.